Pelatihan Pendidikan Seksual pada Siswa SMP di Kota Ambon - Izak Jakobis Makulua; Prisca Diantra Sampe; Rusnawati Ellis; Neleke Huliselan (Kreasi: Jurnal Inovasi dan Pengabdian kepada Masyarakat, 2025)
Sex education is an important thing to teach to teenagers. This is because teenagers are at the genital stage, which makes them want to seek information or try sexual activities. This activity aims to improve students' understanding of sexuality and risky sexual behavior. This activity was carried out for 15 junior high school students in Ambon City. This activity was carried out by delivering material and discussing. The results achieved were that 100% of students understood the material well. This finding indicates that this community service program is effectively implemented for junior high school students